Physical activity and urinary incontinence during pregnancy and postpartum: A systematic review and meta-analysis. (December 2021) - Von Aarburg, Nadine; Veit-Rubin, Nikolaus; Boulvain, Michel; Bertuit, Jeanne; Simonson, Colin; Desseauve, David
Abstract: To assess the association of physical activity and urinary incontinence, or its recovery, during pregnancy and postpartum. A search of publications indexed in five major electronic databases (CENTRAL, PubMed, EMBASE, CINAHL and PEDro) was performed from their respective inception dates to the 30 March 2020 with a combination of keywords to identify studies of interest. Google Scholar was used for non-indexed literature. All studies comparing physical activity with standard care in pregnant and postpartum women were selected. Two reviewers independently selected studies, assessed quality and extracted data. Odds ratios with 95% confidence intervals were calculated using fixed effects or random effects models, for low and moderate heterogeneity between studies, respectively. Seven studies (n = 12479) were included. Data of four studies could be pooled for meta-analyses; subgroup and sensitivity analyses were not possible. Physical activity, either during pregnancy or postpartum, is not associated with urinary incontinence, OR 0.90 (95% CI: 0.69–1.18) and OR 1.31 (95% CI: 0.74–2.34), respectively. Due to a lack of available data, urinary incontinence recovering could not be assessed. The available low evidence does not show that physical activity during pregnancy or postpartum is associated with urinary incontinence. Moderate physical activity should therefore be encouraged for the evidence-based benefits on other obstetrical outcomes.